2019
DOI: 10.1111/jerd.12556
|View full text |Cite
|
Sign up to set email alerts
|

Color change, diffusion of hydrogen peroxide, and enamel morphology after in‐office bleaching with violet light or nonthermal atmospheric plasma: An in vitro study

Abstract: Objective: The aim is to evaluate the effect of violet light (VL) and nonthermal atmospheric plasma (NTAP) combined with or without 35% hydrogen peroxide (HP) and 37% carbamide peroxide (CP).Methods: Bovine crowns were divided into (n = 10) VL, VL/HP, VL/CP, NTAP, NTAP/ HP, NTAP/CP, HP, CP, and C (control) groups. Color and whiteness change (CIELAB-ΔE ab, CIEDE2000-ΔE 00 , whiteness index-ΔWI D ), color parameters (ΔL, Δa, and Δb), and intrapulpal concentration (μL/mL) of HP were assessed by spectrophotometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
2
44
0
4
Order By: Relevance
“…The low-molecular weight of hydrogen peroxide promotes diffusion through interprismatic spaces, which may alter enamel surface morphology. 2,17 Even though this was not the main purpose of this research, it was observed that the combination CP/WT increased Ra in comparison to CP and CP/RT, which is an important evidence corroborating another finding that combination of CP with whitening toothbrushing may compromise enamel Ra. 10 Although SEM analysis of CP/RT indicated continuous irregularity of the enamel surface, it was less pronounced than that of CP/WT group.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The low-molecular weight of hydrogen peroxide promotes diffusion through interprismatic spaces, which may alter enamel surface morphology. 2,17 Even though this was not the main purpose of this research, it was observed that the combination CP/WT increased Ra in comparison to CP and CP/RT, which is an important evidence corroborating another finding that combination of CP with whitening toothbrushing may compromise enamel Ra. 10 Although SEM analysis of CP/RT indicated continuous irregularity of the enamel surface, it was less pronounced than that of CP/WT group.…”
Section: Discussionsupporting
confidence: 82%
“…Simulated toothbrushing with activated charcoal significantly decreased a* values, and this outcome occurred possibly due to the staining protocol adopted with black tea, which deposits extrinsic pigments on the enamel surface. 3,7,17 However, it should be pointed out that isolation of dentin previous to black tea immersion prevented the F I G U R E 2 Mean values and SD of L*, a*, and b* obtained for whitening and toothpaste combinations over time (T B and T 0 ). Means with symbols differ at 5% according to two-way ANOVA and Tukey test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Recent in vitro studies demonstrated that a peroxide-free protocol with violet LED promoted color and whiteness changes in stained teeth. 9,19 Thus, it is expected that LED could prevent damages on enamel surface and the absence of HP and the diffusion of its by-products into the pulp chamber may reduce TS. On the other hand, the mechanism of action of violet LED combined with bleaching gels could be explained by the increase in gels temperature and, consequently, the increase in HP decomposition into free radicals, 2 thereby increasing bleaching efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kury et al 15 (2020), the bleaching treatment with violet LED (VL) showed similar enamel morphology to the untreated group (C), which shows the safety of its use for dental enamel. These similarities were also observed in this study.…”
Section: Discussionmentioning
confidence: 96%